Determinants of Muslims' willingness to pay for halal certified food: Does religious commitment act as a moderator in the relationships?. Issue 6 (12th August 2019) - Parvin Hosseini, Seyed Mehrshad; Mirzaei, Maryam; Iranmanesh, Mohammad
Abstract : Purpose: This study aims to investigate the factors that motivate Muslim consumers to pay for halal-certified food. Design/methodology/approach: Data were collected through a survey of 272 Muslim consumers in Malaysia. The data were analyzed using the partial least squares technique. Findings: The results showed that animal slaughter, halal logo, food quality and religious commitment have a positive effect on the willingness to pay for halal food. Religious commitment positively moderates the relationship between storage and transportation and the willingness to pay for halal-certified food. Practical implications: Policy makers as well as managers of halal food companies can benefit from this study which provides insight into ways to increase demand for halal food. Originality/value: The findings contribute to the literature on halal foods by illustrating the factors that determine Muslim consumers' willingness to pay for halal food. This study also extends the literature by testing the moderating role of religious commitment.